Conscious recall of different aspects of skill memory - Song, Sunbin; Cohen, Leonardo G. (Frontiers in Behavioral Neuroscience, 2014)
Different mechanisms are involved in the formation of memories necessary for daily living. For example, different memory representations are formed for the practiced transitions between key-presses (i.e. pressing key “2” after “3” in “4-3-2-1”) and for the ordinal position of each key-press (i.e. pressing key “2” in the third ordinal position in “4-3-2-1”) in a motor sequence. Whether the resulting transition-based and ordinal-based memories (Song & Cohen, in press) can be consciously recalled is unknown. Here, we studied subjects who over a week of training and testing formed transition and ordinal-based memory representations of skill for a 12-item sequence of key-presses. Afterwards, subjects were first asked to recall and type the trained sequence and then to perform random key-presses avoiding the trained sequence. The difference in the ability to purposefully recall and avoid a trained sequence represents conscious recall (Destrebecqz & Cleeremans, 2001). We report that (a) the difference in the ability to purposefully recall and to avoid the trained sequence correlated with ordinal-based but not with transition-based memory, (b) subjects with no ability to recall or avoid the trained sequence formed transition-based but not ordinal-based memories, and (c) subjects with full ability to recall and avoid the trained sequence formed both transition-based and ordinal-based memories. We conclude that ordinal-based memory can be voluntarily recalled when transition-based memory cannot, documenting a differential capacity to recall memories forming a motor skill. Understanding that different memories form a motor skill, with different neural substrates (Cohen & Squire, 1980), may help develop novel training strategies in neurorehabilitation of patients with brain lesions.